Uses of Diagnostic Ultrasonography in the Diagnosis of Some Digestive Disorders in Cattle and Buffalo - Abd El Razik, Wafaa M.; Al Nagar, Al Abbas M.A.; Kotb, Amr G.A.; Gouda, Shaimaa M.A. (Journal of Advanced Veterinary Research, 2023)
The bovine sector represents an important part of the animal resources in Egypt, as it plays important role in supplying humans with a considerable part of their daily needs of animal-derived proteins via their milk and meat. However, such animal species can be exposed during their life to a wide range of digestive disorders, which affect animal performance and productivity. Ultrasonography plays an essential role in the accurate and rapid diagnosis of several diseases affecting cattle and buffaloes. In this review, we will highlight the role of ultrasonography in the diagnosis of digestive disorders in cattle and buffaloes.